Desarrollo e implementación de una metodología para planeación y evaluación de acciones de mitigación de emisiones GEI en procesos logísticos industriales : caso de estudio : empresa del sector avícola (2017)
The companies face the need to plan in the short, medium and long term the actions required for the decarbonization of their productive and logistic operations. Allowing them to prepare for the adaptation and gradual transformation of their processes, in the face of possible changes in supply chains due to future restrictions on the use of fossil fuels. This is necessary for the achievement of the global goals of reducing greenhouse gas emissions, which lead to the slowdown of climate change. This paper proposes a methodology for a company, based on the quantification of its current GHG emissions, to select the most appropriate mitigation measures for its logistical processes, plan its implementation, estimate the impact on the reduction of GHG emissions and calculate some co-benefits for the company and society. We present the results of a case study, which shows the implementation of the planning methodology in a company of the Colombian poultry sector.